Pengaruh Implementasi SIMDA, Kinerja Aparatur Pemerintah Daerah dan Penerapan SAP Terhadap Kualitas LKPD Lombok Tengah - Azzindani, Rahmatia; Pituringsih, Endar; Irwan, M (E-Jurnal Akuntansi; Vol 27 No 1 (2019)DO - 10.24843/EJA.2019.v27.i01.p16, 2019)
The study aims to prove empirically the effect of the implementation of   SIMDA on the quality of LKPD , the influence of the performance of regional government officials on the quality LKPD , and the SAP on the quality of LKPD . Sources of data in the study used a questionnaire distributed to 32 ODP s in Central Lombok Regency. The results of (H 1 ) and (H 2 ) for the implementation of   SIMDA (X 1 ) and (X 2 ) indicate that the variable implementation of SIMDA has a significant effect on the quality of LKPD and a positive t-value indicates that the implementation of SIMDA has a relationship in line with the quality of LKPD . As well as the results of research from the testing of the third hypothesis (H 3 ) for the variable application of SAP (X 3 ) shows that the application of SAP does not have a significant effect on the quality of LKPD and t-value positively indicates that the application of SAP has a relationship which is in line with the quality of LKPD . Keywords : Implementation of SIMDA , Performance of Local Government Apparatus, Application of SAP, Quality of LKPD